Taṭwīr an-Namūżaj li Ta’līm Mahārah al-Kalām ‘alā Asās at-Tanwīm al-Magnāṭīsīy at-Ta’līmīy (Hypnoteaching) bi Daurah Ta’līm al-Lugah al-‘Arabiyyah al-Mukaṡṡafah Masqot Dirghoem Academy Pare Kediri Jawa as-Syarqiyyah - Inchinia Angger Rowin; Asmaul Husna Az-Zain (Arabic Education Program IAIN Pekalongan, 2022)
This research aims to develop a model of teaching speaking skill, know the validity of a model of teaching, and measure the effectiveness of a model of teaching speaking skill based on hypnoteaching. This research is a type of research and development (R&D) that took six steps of product development, adopted from the book Borg and Gall. The researcher uses various data collection methods, including observation, interview, questionnaire, and test. The researcher analyzes the qualitative data on the interactive model by Miles and Huberman and the quantitative data on the percentile and the mean formulation. The results of the research are: First, the developed teaching model is distinguished by hypnoteaching specifications, which include the following five contents: preliminary, integration of the concept of speaking skill and hypnoteaching, characteristics of teaching model implementation, components of teaching model activities, and types of teaching model speaking skill based on hypnoteaching. Second, the developed teaching model is valid to be applied. It emerged from the results of the questionnaire for the contents of the teaching model. It shows 94.5% and 97.7%, indicating that the education model's assessment of speaking skill is